Sete til ishockeykjelke - Ålgård, T. (2014)
Ice sledge hockey is a modified version of regular ice hockey, targeting athletes with lower body mobility impairments. A sledge is used as an adaptive device and two composite sticks enable for puck handling and player movement. In order to ootimize the complex movements in the sport the transfer of forces from the athlete to the ice should be optimized. The seat is a critical compo-nent in this optimization and requires special attention in terms of how it is adapted to fit each individual athlete. During the last years there has been a significant improvement in the equipment used by other national teams, but the Norwegian team has been using sledges that have become increasingly out-dated and therefore have not been part of this development in full. In the same period the Norwegian sledge manufacturer has experienced a substantial decline in sales, where the increased performance of competing products is regarded as one of the main factors. The main focus of this master thesis has thereforebeen the development of a new and improved seat for ice hockey sledges, which enables the customization for each individual athlete, while still being able to be produced in a cost-efficient manner on a small scale. The possibility of seat customization from the four major sledge manufacturers where identified, in terms of which changes could be made at the time of ordering and how they would affect the design. Furthermore, an analysis was done in order to assess which parameters are expected to vary the most amongst the different athletes, in terms of anatomical measurements, effects from the specific impairment and the athletes' individual preferences. An identification of the seats functional surfaces was performed and specialized tools for measuring the athletes were developed. Anatomical data from half of the athletes of the Norwegian national team was gathered and the results systemized. A system was developed to determine the desired location of the seat's functional surfaces based on the anatomical measurements of the athlete, effects from his impairment, and his personal preferences. Resulting from the analysis are two separate concepts of individualized seats and their respective production setups. Concept 1 comprises of an adjustable vacuum forming tool to formseats from a plastic material and where the main variations between the athletes' anatomical measurements are met by adjusting the tool. Concept 2 comprises of a seat assembled from three individual components. Two side panels made from vacuum formed plasticmaterial that are mounted to a centerpart made from a carbon fiber composite sandwichstructure, and the athletes' specific requirements are fulfilled through the assembly process. The main difference between the concepts, in terms of implementation of the production, lies in the amount of manual effort that is required to attain the high level of individualization; Concept 1 requires manual adjustments in the vacuum forming facility and Concept 2 requires adjustments while assembling pre-made components.